A hybrid approach based on ARIMA and artificial neural networks for crime series forecasting [electronic resource] - Mohd. Suhaimi Mohd. Zaki, 1981- author; Mohamad Shukor Talib; Fakulti Komputeran (2014)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2014